CAPACITY, POTENTIAL, AND ABILITY: INTEGRATING DIFFERENT APPROACHES TO STUDYING ANIMAL VS HUMAN CREATIVE PROCESSES - James C Kaufman; Allison B Kaufman (Peoples' Friendship University of Russia (RUDN University), 2016)
For all of the differences between studying animal and human creativity and innovation, there are enough similarities that we can gain insight by integrating both perspectives. Both research approaches focus on creative ability, but animal studies favor the concept of creative capacity whereas human scholars prefer the idea of creative potential. We explore here the implications of these differences and what each field can learn from the other.